Degree-Day Index for Estimating the Thermal Requirements of a Greenhouse Equipped with an Air-Earth Heat Exchanger System - H Faridi; A Arabhosseini; Gh Zarei; M Okos (Journal of Agricultural Machinery, 2021)
In this research, an attempt was made to utilize an Earth-Air Heat Exchanger (EAHE) system as a source of shallow geothermal energy to provide thermal demands of a commercial greenhouse located in Alborz province, Iran. The degree-day index was applied to estimate the EAHE system’s potential to meet the thermal requirements of the greenhouse including cooling and heating demands. The results indicated that this region needed more energy to reach to the relevant temperature inside the greenhouse for the heating demand comparing to the cooling one. The average potential of the EAHE system based on the degree-day index was 10.76ºC for increasing temperature in the cold and 17.96ºC for decreasing temperature in the warm season. This means that the EAHE system was capable of supplying the greenhouse thermal demands in this area according to the calculated values of Heating Degree-Day (HDD) and Cooling Degree-Day (CDD). This method would be beneficial in monitoring and optimizing plant growth conditions as the best crop type or cultivation selection which in turn can help in irrigation and fertigation management of the crop grown.